(3GdJCejf ef GdfGMjI GdeMGSHjI h GdJObjbjIs - (3NGdO QGZH(B, (3GdNWjHs ((3YeGf(B:s (3OGQ cfhR GdeYQaI GdYdejI ddfTQ hGdJhRjY(B,s, 2009)
(3GdaUd GdChd (B: (3JegjO (B: (3YedjGJ GdJCejf Ydi GdMjGI hJchjf GdCehGd (B: (3YedjGJ EYGOI GdJCejf (B: (3GdMSGHGJ GdNJGejI hGdejRGfjI aj TQcGJ GdJCejf (B: (3GdeMGSHI aj TQcI GdJCejf(B-(3GdaUd GdKGfj (B: (3eOi JWHjb eYGjjQ GdJObjb GdOGNdj GdeJYGQa YdjgG aj GdTQcGJ GdJCejfjI GdCQOfjI(B-(3GdaUd GdKGdK (B: (3GdJObjb GdOGNdj(B-(3GdaUd GdQGHY (B: (3eYGjjQ hELQGAGJ hbhGYO GdSdhc Gdegfj ddJObjb GdOGNdj(B-(3GdaUd GdNGeS (B: (3eaGgje hCSGSjGJ YGeI hYhGed fThA hJWhQ GdEOGQI GdeGdjI GdOhdjI(B. (3edNU(B: (3jJfGhd gPG GdcJGH YedjGJ bSe GdJCejf Ydi GdMjGI hJchjf GdGehGd (B? (3YedjGJ GYGOI GdJCejf (B? (3GdMSGHGJ GdNJGejI hGdejRGfjI aj TQcGJ GdJCejf (B? (3GdeMGSHI aj TQcGJ GdJCejfs
(3HHdjhZQGajG(B: (3U(B.223s
Keywords: (3GdJCejf `` GdGQOfs; (3GdJCejf (B- (3GdHfhcs; (3GdJCejf Ydi GdMjGIs; (3GdeMGSHI hGdJCejfs